Compliance to Treatment Regimen among Patients with Diabetes attending out Patient Department of a Referral Hospital in Kathmandu - Nirmala, Dhital; KC, Takma; Mukhia, Suzanna (Journal of Nursing Education of Nepal, 2023)
Diabetes is a chronic metabolic disorder which causes significant morbidity and mortality throughout the world. Control and prevention of complications is mainly based on patients’ compliance to treatment regimen which includes life-style modification. This study was aimed to assess the level of compliance and its association with selected variables. A descriptive cross-sectional design was adopted to conduct the study among 203 diabetic patients in Tribhuvan University Teaching Hospital in specific areas: Medication, Exercise, Follow up and Diet. Data were collected using purposive sampling technique through semi-structured interview schedule and were analyzed by using the descriptive statistic (frequency, percentage, mean and standard deviation) and inferential statistic (chi-square). This study revealed that the medicine compliance levels for good, fair and poor compliance were 62.1%, 31.5% and 6.4% respectively. Similarly the exercise compliance levels were 31.5%, 39.4% and 29.1%and the follow-up compliance were 65.5%, 5.9% and 28.6%. The dietary compliance levels were 77.3%, 21.7% and 1.0% for good, fair and poor respectively. Compliance to medicine was associated with educational status (p=0.040) and the area of residence (p=0.023). Compliance to follow up was associated with diabetic counseling (p=0.028%). Dietary compliance was associated with family income (p=0.035) and dietary counseling (p=0.001). The study concluded that the respondents who had enough monthly income and received dietary counseling had good compliance in diet. Those who received diabetic counseling also had good compliance in follow-up. The findings suggest that blood sugar can be controlled by enhancing compliance in the diabetic treatment regimen. Thus it is strongly recommended that the need of proper counseling regarding diet, medicine, exercise and follow-up in all health care settings for patients with diabetes.